knowledge, attitudes and practices of rural men towards the use of contraceptives in Ga-Sekororo, Limpopo Province, South Africa - Matlala, Sogo France (University of Limpopo, 2015)
In rural areas, most women carry the burden of preventing unwanted pregnancies alone. Most of the men are not aware of the benefits of contraceptives. They mostly complain that the contraceptives their partners use make them sick. Men have a negative attitude towards the use of contraceptives and do not share the responsibility of contraceptive use with their partners. Aim: Aim of this study was to determine men’s knowledge, practices, and attitudes on the use of contraceptives in a village of Limpopo province, South Africa. Methods: Five focus group discussions were held with groups of men between the ages of 20 and 50 in the five villages of Ga-Sekororo. The researcher used an audio tape to record what participants said during group sessions and made some observational notes to supplement the tape recordings. The researcher used a topic guide to direct and guide sessions with each of the group meetings in order to understand their knowledge, practices, and attitudes towards the use of contraceptives. Results: Some of the men were able to list the various methods of contraceptives available, the benefits of contraception, and the negative consequences of unprotected sex. Only 32% indicated a willing ness to use a male contraceptive pill when available which indicated unwillingness in most men to share the responsibility of contraception with their partners in spied of their knowledge of the benefits of contraception. Ninety two percent of men prefer the first-born child to be a male and if it happens to be a female, will continue to have children until a male is born. Programmes to address the reproductive health needs of men are needed and when implemented will benefit women as well. The government and non-governmental organizations (NGOs) should work together to fulfil this need.
Thesis (M.Sc. (Public Health)) --University of Limpopo, 2005
Keywords: Rural men; Contraceptives; 363.960968; Birth control -- South Africa; Men -- Sexual behavior -- South Africa; Men -- Contraceptives -- Attitudes; Public Health